Patient File System - Abd-alwanes Dinaly, Fathya (Libyan International Medical University, 2016)
Health information technology (HIT) : is information technology applied to health and health care. It supports health information management across computerized systems and the secure exchange of health information between consumers, providers, payers, and quality monitors. Based on an often-cited 2008 report on a small series of studies conducted at four sites that provide ambulatory care–three U.S. medical centers and one in the Netherlands– the use of Electronic Health Records (EHRs) was viewed as the most promising tool for improving the overall quality, safety and efficiency of the health delivery system, broad and consistent utilization of HIT will: • Improve health care quality or effectiveness. • Increase health care productivity or efficiency. • Prevent medical errors and increase health care accuracy and procedural correctness. • Reduce health care costs. • Increase administrative efficiencies and healthcare work processes. • Decrease paperwork and unproductive or idle work time. • Extend real-time communications of health informatics among health care professionals; and Expand access to affordable care. We don’t doubt that health informatics is very common and helpful which the services are much better and tasks are more easier ,in this project I will do the patients files system which helps the center to save time and cost and lack of contradiction patient data.